2020
DOI: 10.3390/ijerph17155392
|View full text |Cite
|
Sign up to set email alerts
|

Role of Global Self-Esteem in Predicting Life Satisfaction of Nursing Students in Poland, Spain and Slovakia

Abstract: Background: This study analyzed the role of global self-esteem and selected sociodemographic variables in predicting life satisfaction of nursing students in Poland, Spain and Slovakia. Methods: The study subjects were full-time nursing students from three European countries. A diagnostic survey was used as a research method, while the Rosenberg self-esteem scale (SES) and the satisfaction with life scale (SWLS) were used to collect data. Results: The research was performed on a group of 1002 students. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
(37 reference statements)
1
10
0
2
Order By: Relevance
“…The age of the students was analyzed in three age groups, assuming the following ranges: ≤20 years ( n = 401; 40.02%), 21–22 years ( n = 410; 40.92%) and ≥23 years ( n = 191; 19.06%). The presented data are part of a larger international project and detailed sociodemographic characteristics are also included in other publications [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The age of the students was analyzed in three age groups, assuming the following ranges: ≤20 years ( n = 401; 40.02%), 21–22 years ( n = 410; 40.92%) and ≥23 years ( n = 191; 19.06%). The presented data are part of a larger international project and detailed sociodemographic characteristics are also included in other publications [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Self-esteem is an important psychological resource and has been demonstrated to be a mental health protector against academic burnout (Luo et al, 2016). In addition, empirical research has also confirmed the positive association of self-esteem with life satisfaction (Kupcewicz et al, 2020) and the negative correlation of selfesteem with maladaptive perfectionism (Mirzairad et al, 2017). Therefore, we hypothesized that self-esteem, as a moderator, may affect the mediating role of academic burnout in the relationship between maladaptive perfectionism and life satisfaction among medical students.…”
Section: Introductionmentioning
confidence: 91%
“…In the study by Turan et al (2020), the average life satisfaction of students of nursing was found to be high (22.72 ± 6.45). The comparison of the life satisfaction of students of nursing from three different countries, revealed that life satisfaction was higher in Spain than in Poland or Slovakia (Kupcewicz et al, 2020). Satisfaction with life is a subjective feeling and is defined as the individual's positive evaluation of their life according to the criteria they have determined (Tian et al, 2018).…”
Section: Discussionmentioning
confidence: 99%